Pedagogical Methods Of Teaching Mathematics In Distance Learning (Texas Journal of Multidisciplinary Studies, 2022)
During the global pandemic, humanity has once again proved that many actions are convenient to perform remotely, and not directly. At a time when it was unclear how long the pandemic process would continue around the world, it was certainly necessary that other social processes in our daily lives continue. At such a moment, the education system should not have stopped either. The concept of distance learning has once again proved its relevance at the present time. The article provides feedback that it is through distance learning that the most difficult subject among subjects is taught mathematics. The relevance and degree of study of the topic of the article are revealed using scientific developments of foreign scientists.